RNA ISOLATION OF DENGUE VIRUS TYPE 1 WITH DIFFERENT PRECIPITATION SOLVENTS: DIMETHYL SULFOXIDE, ACETONE, AND ETHANOL 70% - Maharani, Anisa; Sucipto, Teguh Hari; Setyawati, Harsasi; Churrotin, Siti; Amarullah, Ilham Harlan; Wardhani, Puspa; Aryati, Aryati; Ueda, Shuhai; Soegijanto, Soegeng (Indonesian Journal of Tropical and Infectious Disease, 2018)
Dengue Hemorrhagic Fever (DHF) is caused by dengue viruses that belong to Flaviviridae. The disease is known to be caused by 4 types of dengue viruses, namely DENV-1, DENV-2, DENV-3, and DENV-4 associated with antigenic. Dengue virus is a virus RNA that causes illness with clinical manifestations of Dengue Fever, Dengue Hemorrhagic Fever and Dengue Shock Syndrome. The aim of research was to determine the effectiveness of dimethyl sulfoxide, acetone, and ethanol 70% as precipitation solvent in the process of RNA isolation. The method used was Reverse Transcription - Polymerase Chain Reaction (RT-PCR) and Polymerase Chain Reaction (PCR) with specific primers for dengue virus type 1 (DENV-1). RNA isolation can be done easily using an RNA Isolation Kit. Use of RNA Isolation Kit results in a purer RNA isolate from contaminants and from RNA degradation. In generally the isolation is using cold ethanol / alcohol with concentration 90-95%. Ethanol / Alcohol does not dissolve RNA and light density of alcohol lighter than water makes RNA rise and hover on the surface. In RNA isolation solvent precipitation that used are acetone, ethanol 70%, and DMSO. In qualitative RNA measurements using agarose gel electrophoresis and was examined under the UV light-illuminator and quantitative RNA measurements using Nanodrop spectrophotometry with absorbance ratio at 260/280 and 260/230 showed a good result indicated by the appearance of the band on electrophoresis results in PCR. While the measurement quantitatively is showed that there was still protein contamination but the results are quite good because it does not much different from the ratio set in the reference. Acetone, ethanol 70%, and DMSO can be used as a substitute of 96% ethanol in the process of RNA isolation in DENV-1 virus and can also be applied to other dengue virus because the structure of the 4th antigen serotype is very similar one with the other and no effect.